O38. Radiosensitivity of CD34+ hematopoietic stem and progenitor cells: A target for radiation-induced leukemia. (September 2016) - Vandevoorde, C.; Thierens, H.; Vral, A.; Vandekerckhove, B.; Slabbert, J.P.
Abstract : Introduction: Due to their long life span, accumulation of DNA damage in stem cells can compromise their genomic integrity. Hematopoietic stem and progenitor cells (HSPCs), characterized by the cell surface marker CD34, may be a major target for radiation-induced leukemogenesis. Secondary leukemia risks are especially important for childhood cancer survivors treated with radiotherapy, since epidemiological data indicate that the risk for radiation-induced hematological malignancies is 3–5 times higher for children compared to adults. In order to investigate the underlying mechanism of radiation-induced leukemia, an in vitro study of the radiation effects in CD34+ cells was performed. Materials and Methods: Human CD34+ HSPCs were isolated from umbilical cord blood by using CD34+ immunomagnetic beads (Miltenyi). Peripheral blood T-lymphocytes were isolated from healthy adults using RosetteSep TM human T-cell enrichment cocktail (Stemcell). Radiation-induced DNA double-strand breaks (DSBs) were assessed by microscopic scoring of γ -H2AX/53BP1 foci 0.5h after low-dose x-ray exposure, while DNA repair was evaluated by scoring residual γ -H2AX/53BP1 foci 24h after 4 Gy x-ray exposure. A micro-culture cytokinesis block micronucleus (MN) assay was developed for CD34+ cells in order to study radiation-induced mutagenic effects after 2 Gy x-ray exposure. Results: HSPCs show significantly lower endogenous levels of DNA DSBs and MNi compared to adult T-lymphocytes. No statistical significant difference could be observed in the number of DNA DSBs induced by low-dose x-rays (100 and 200 mGy) between HSPCs and T-lymphocytes. However, the number of residual DNA DSBs 24h post-exposure was significantly lower in HSPCs (3.54 foci/cell) compared to T-lymphocytes (5.77 foci/cell). Furthermore, HSPCs showed a significantly higher number of MNi (371MN/1000BN cells) compared to T-lymphocytes (275MN/1000BN cells). Conclusion: The low number of residual DNA DSBs 24h post-exposure and the high number of radiation-induced MN yields in HSPCs indicate fast error-prone DNA repair and mutagenesis after radiation exposure, which could trigger leukemia development.